Diplomasi Olahraga dalam Asian Games 2018 sebagai Instrumen Nation Branding dan Penguatan Middle Power Indonesia di Asia: Sports Diplomacy in the 2018 Asian Games as an Instrument for Nation Branding and Strengthening Indonesia's Middle Power in Asia - Yarham Harid; Stivani Ismawira Sinambela (Anterior Jurnal, 2026)
In the modern era, sports are no longer merely understood as a competitive arena, but also as a strategic diplomatic tool to strengthen international relations and promote culture. Indonesia used the 2018 Asian Games in Jakarta and Palembang to emphasize the role of sports diplomacy as part of its soft power, public diplomacy, and middle-power diplomacy strategies. This research analyzes Indonesia's sports diplomacy to strengthen nation branding and its position as a middle power in Asia, and to affirm cultural identity through the 2018 Asian Games. The methodology used is a descriptive, qualitative, desk study approach, which allows for in-depth analysis of academic literature, official reports, and other relevant secondary sources. The research findings show that the 2018 Asian Games successfully enhanced Indonesia's positive image, introduced its cultural richness through performing arts and traditional sports, and strengthened its position as a middle power in Asia. Thus, the 2018 Asian Games confirmed that sports can serve as an essential instrument in enhancing Indonesia's cultural diplomacy and international relations, while also strengthening its position on the global stage. However, sports diplomacy has limitations, as its influence tends to be temporary if not supported by a sustainable foreign policy strategy.